Efficacy of lithium in the treatment of Alzheimer's disease: scientific evidence (Research, Society and Development, 2019)
The present study had as objective to verify the effectiveness of the use of lithium in the treatment of Alzheimer's Disease. It is a review of the integrative type, using articles published in the years 2011 to 2014, available in PubMed, ScienceDirect and Scielo databases. Recent studies have shown that dietary supplementation with lithium prevented the increase of inflammatory mediators in the rat brain, leading to apparent therapeutic neuroprotective effects of lithium. It also leads to increased neurogenesis in the hippocampal gyrus and appears to increase gray matter, evidence that lithium has a neuroprotective action in the treatment of symptoms associated with Alzheimer's disease. It was observed that the use of lithium in the treatment of Alzheimer's disease has some positive effects, however, more detailed studies are needed.